Epoxy resin for high-voltage direct current based on in-situ generated Cu2S nanoparticle modification and preparation method thereof
By generating Cu2S nanoparticles in situ in epoxy resin, the problem of nanoparticles being easily agglomerated in high-voltage DC environment is solved, and their uniform dispersion and interface combination are achieved, the insulation performance and mechanical strength are improved, and the dielectric loss and corona discharge risk are reduced.
Patent Information
- Application Number
- CN202411673846.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
In a high-voltage DC environment, nanoparticles are prone to agglomeration in epoxy resin, resulting in poor dispersion, affecting insulation performance and mechanical strength, and not closely interacting with each other, increasing dielectric loss and local discharge risks.
Cu2S nanoparticles are generated in situ in the epoxy resin and nanoparticles are generated by decomposition of N,N-dibutyldithiocarbamate, which achieves uniform dispersion and enhances the binding of nanoparticles with epoxy resin through interface wetting.
The uniform dispersion of nanoparticles is achieved, the insulation performance and mechanical strength of epoxy resin are improved, the dielectric loss and corona discharge risks are reduced, and the insulation reliability is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-voltage direct current insulating epoxy resins, and in particular relates to an epoxy resin for high-voltage direct current modified based on in-situ generated Cu2S nanoparticles and a preparation method thereof. Background Art
[0002] In the context of the current global energy structure transformation and the continuous growth of electricity demand, high-voltage direct current (HVDC) technology is becoming increasingly important as a key means to achieve long-distance, large-capacity power transmission and grid interconnection. With the rapid development of renewable energy, such as the large-scale access of distributed energy such as wind power and solar energy, and the increase in the demand for cross-regional energy allocation, HVDC technology can not only effectively reduce energy loss in the transmission process and improve transmission efficiency, but also promote the efficient development and extensive use of clean energy, which is of great significance for building a green, low-carbon and efficient energy system. In this process, as a key component to ensure the safe and stable operation of power equipment, the improvement of the performance of insulation materials is directly related to the reliability and economy of the entire transmission system.
[0003] Epoxy resin, with its excellent mechanical strength, good corrosion resistance and excellent insulation performance, has become an indispensable insulating support material in high-voltage direct current transmission equipment. In particular, epoxy resin is widely used in key components such as DC gas insulated switchgear (GIS / GIL), insulating pull rods and wall bushings. In order to further improve the insulation performance of epoxy resin in high-voltage direct current environments, researchers have carried out extensive research. On the one hand, by modifying the epoxy resin body, such as introducing special functional groups, adjusting the cross-linking density or using new curing agents, higher insulation resistivity and lower dielectric loss can be obtained. On the other hand, by physical blending or chemical grafting, micro-nano particles (such as silica, alumina, graphene, etc.) are uniformly dispersed in the epoxy resin matrix, and the special properties of these particles are used to enhance the insulation performance and thermal stability of the composite material, providing a new material basis for the development of high-voltage direct current transmission technology.
[0004] Although the introduction of micro-nanoparticles provides an effective way to improve the insulation performance of epoxy resin, it still faces many challenges in practical application. The primary problem is the dispersibility of nanoparticles. Since nanoparticles have extremely high specific surface area and large surface energy, they are very easy to agglomerate when preparing composite materials, which not only affects the uniform distribution of particles in epoxy resin, but also may cause defects inside the material, which in turn reduces the insulation performance and mechanical strength of the composite material. In addition, the interfacial interaction between nanoparticles and the epoxy resin matrix is also a key factor affecting the performance of composite materials. If the interface is not tightly bonded, it may cause charge accumulation at the interface, increase dielectric loss, and even cause partial discharge, posing a threat to the long-term safe operation of the equipment. Therefore, how to effectively solve the dispersion problem of nanoparticles and optimize the interface bonding between particles and the matrix has become a technical problem that needs to be solved in the current research on improving the insulation performance of epoxy resin. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an epoxy resin for high-voltage direct current modified by in-situ generated Cu2S nanoparticles and a preparation method thereof, so as to solve the technical problem that nanoparticles are easy to agglomerate in epoxy resin, achieve uniform dispersion of nanoparticles, and improve the insulation performance of epoxy resin under high-voltage direct current.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses an epoxy resin for high voltage direct current modified by in-situ generated Cu2S nanoparticles, comprising epoxy resin, filler, curing agent and accelerator; the filler comprises basic filler and reinforcing filler; the basic filler is Al2O3 micron particles; the reinforcing filler is Cu2S nanoparticles; the Cu2S nanoparticles are prepared by in-situ reduction of N,N-dibutyl copper dithiocarbamate in epoxy resin.
[0007] Preferably, the mass ratio of epoxy resin, Al2O3 micron particles, N,N-dibutyl copper dithiocarbamate, curing agent and accelerator is (90-110): (100-200): (3-15): (60-80): 1.
[0008] Preferably, the epoxy resin is any one of bisphenol A epoxy resin E51 and bisphenol A epoxy resin E42.
[0009] Preferably, the curing agent is any one of anhydride curing agent, tetrahydrophthalic acid, hydrogenated phthalic acid and maleic anhydride.
[0010] Preferably, the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0011] The present invention also discloses a method for preparing the above-mentioned high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, comprising: dissolving the epoxy resin in a mixed solvent of DMF and NMP, and fully stirring until dissolved; adding N,N-dibutyl copper dithiocarbamate, stirring evenly at high speed, and performing secondary dispersion by ultrasound; after temperature reaction, heating and stirring until the solvent is completely volatilized to obtain the epoxy resin containing the in-situ generated Cu2S nanoparticle reinforced filler; then adding a curing agent, an accelerator and Al2O3 micron particles, stirring evenly, placing in a mold, performing vacuum degassing and high-temperature curing, and then demolding to obtain the high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles.
[0012] Preferably, the mass ratio of epoxy resin, Al2O3 micron particles, N,N-dibutyl copper dithiocarbamate, curing agent and accelerator is (90-110): (100-200): (3-15): (60-80): 1; the volume ratio of DMF and NMP is (80-120): (80-120) and the stirring temperature is 70-100°C.
[0013] Preferably, the temperature-raising reaction conditions are: raising the temperature to 160-200° C. at a heating rate of 1-2° C. / min and keeping the temperature for 3-6 hours.
[0014] Preferably, the temperature of heating and stirring is 70-90°C; the conditions for vacuum degassing are: degassing at 100-120°C for 25-45min; the conditions for high temperature curing are: 110-130°C for 70-110min, then heating to 155-175°C for 90-130min, and finally heating to 185-205°C for 80-120min.
[0015] Preferably, 1 mol of N,N-dibutyl copper dithiocarbamate generates 1 mol of Cu2S nanoparticles.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles. The uniformly dispersed Cu2S nanoparticles are generated in-situ inside the epoxy resin matrix and can act as carrier traps, so as to facilitate the casting of large-scale insulating parts and improve the insulation performance of the material. The technology of in-situ generation of nanoparticles in epoxy resin can make the nanoparticles uniformly dispersed in the epoxy resin matrix, and the dispersibility is greatly improved compared with direct addition; the decomposition products of N, N-dibutyl dithiocarbamate copper are contained around the Cu2S nanoparticles, which can enhance the interface wettability between the nanoparticles and the epoxy matrix; the Cu2S nanoparticles are used as reinforcing fillers, which can form carrier traps at the interface and enhance the DC resistivity on the one hand, and can disperse the electric field in the epoxy resin as a semiconductor on the other hand, reduce the local electric field strength, thereby reducing the risk of corona discharge and improving the insulation reliability.
[0017] The present invention also discloses a method for preparing the above-mentioned high-voltage direct current epoxy resin modified by in-situ generation of Cu2S nanoparticles. The epoxy resin is dissolved by selecting a suitable solvent (a mixed solvent of DMF and NMP) to provide a basis for subsequent steps. N, N-dibutyl copper dithiocarbamate is added, and under the action of high-speed stirring and ultrasonic dispersion, it is ensured to be uniformly distributed in the epoxy resin, providing conditions for subsequent reactions to generate Cu2S nanoparticles. Through a temperature-raising reaction, N, N-dibutyl copper dithiocarbamate is decomposed and Cu2S nanoparticles are generated in-situ. Subsequently, the solvent is completely volatilized by heating and stirring to obtain an epoxy resin containing Cu2S nanoparticles. By adding a curing agent, an accelerator and Al2O3 micron particles, and through the steps of uniform stirring, vacuum degassing and high-temperature curing, the desired modified epoxy resin is finally obtained. Through the in-situ generation technology, the uniform dispersion of Cu2S nanoparticles in the epoxy resin is achieved, and the problem of easy agglomeration of nanoparticles in the traditional addition method is avoided, thereby improving the insulation performance of the composite material. Cu2S nanoparticles act as carrier traps, which can effectively enhance DC resistivity and improve insulation performance. At the same time, as a semiconductor material, it can also disperse the electric field in the epoxy resin, reduce the local electric field strength, and thus reduce the risk of corona discharge. The high-voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles obtained by the above modification method has higher insulation performance and reliability, and is suitable for application scenarios requiring high insulation performance such as high-voltage direct current transmission. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those described herein. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0020] The present invention is described in further detail below in conjunction with embodiments: The invention discloses an epoxy resin for high voltage direct current modified by in-situ generated Cu2S nanoparticles, comprising: epoxy resin, filler, curing agent and accelerator; the filler comprises basic filler and reinforcing filler; the basic filler is Al2O3 micron particles; the reinforcing filler is Cu2S nanoparticles; the Cu2S nanoparticles are prepared by in-situ reduction of N,N-dibutyl copper dithiocarbamate in epoxy resin.
[0021] Among them, epoxy resin (90-110 parts), Al2O3 micron base filler (100-200 parts), N,N-dibutyl copper dithiocarbamate (3-15 parts), curing agent (60-80 parts), and accelerator (1 part).
[0022] The epoxy resin is a bisphenol A epoxy resin, and any one of E51 and E42 is selected.
[0023] The curing agent is any one of an acid anhydride curing agent, tetrahydrophthalic acid, hydrogenated phthalic acid and maleic anhydride.
[0024] The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0025] The in-situ generation of Cu2S nanoparticle reinforced filler comprises the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP, keep the temperature at 70-100°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and N,N-dibutyl copper dithiocarbamate into a reaction kettle, heating to 160-200°C at a heating rate of 1-2°C / min, and then maintaining at 160-200°C for 3-6 hours to complete the reaction; 4) After the above reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 70-90° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0026] In step 1), the volume ratio of DMF to NMP is (80-120): (80-120), and the stirring temperature is 70-100°C.
[0027] In step 2), copper N,N-dibutyldithiocarbamate can be completely reacted, and 1 mol of copper N,N-dibutyldithiocarbamate generates 1 mol of Cu2S nanoparticles.
[0028] In step 3), the reaction time is 3-6 hours, the reaction temperature is 160-200°C, and the heating rate is 1-2°C / min.
[0029] Then, the epoxy resin containing in-situ generated Cu2S nanoparticles reinforced filler, curing agent and accelerator are placed in a high-speed mixer, Al2O3 micron filler is added, and the mixture is stirred evenly at 70-90°C, and then the mixture is observed to be evenly dispersed. Then the mixture is placed in a mold, degassed at 100-120°C for 25-45 minutes, and vacuum degassing is performed; 110-130°C for 70-110 minutes, then heated to 155-175°C for 90-130 minutes, and finally heated to 185-205°C for 80-120 minutes for high-temperature curing; then demolding is performed to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and resistivity testing is performed.
[0030] Example 1 A method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles comprises the following steps: First, prepare 90 parts of epoxy resin E51, 100 parts of Al2O3 micron base filler, 3 parts of N,N-dibutyl copper dithiocarbamate, 60 parts of tetrahydrophthalic acid, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0031] In situ generated Cu2S nanoparticle reinforced filler was prepared by the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP (volume ratio of 100:100), keep the temperature at 80°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and copper N,N-dibutyldithiocarbamate into a reaction kettle, heating it to 180°C at a heating rate of 1°C / min, and then maintaining it at 180°C for 3 hours to complete the reaction; 4) After the above reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 80° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0032] Then, the epoxy resin, curing agent and accelerator containing in-situ generated Cu2S nanoparticles reinforced filler were placed in a high-speed mixer, Al2O3 micron filler was added, and the mixture was stirred evenly at 80°C, and then observed whether the mixture was evenly dispersed. The mixture was then placed in a mold, degassed at 110°C for 30 minutes, and vacuum degassing was performed; 120°C for 90 minutes, then heated to 165°C for 110 minutes, and finally heated to 195°C for 100 minutes for high-temperature curing, and then demolded to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and the resistivity test was performed.
[0033] Example 2 A method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles comprises the following steps: First, prepare 110 parts of epoxy resin E42, 200 parts of Al2O3 micron base filler, 5 parts of N,N-dibutyl copper dithiocarbamate, 70 parts of hydrogenated phthalic acid, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0034] In situ generated Cu2S nanoparticle reinforced filler, which is prepared by the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP (volume ratio of 100:100), keep the temperature at 80°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and copper N,N-dibutyldithiocarbamate into a reaction kettle, heating it to 180°C at a heating rate of 1.5°C / min, and then maintaining it at 180°C for 6 hours to complete the reaction; 4) After the above reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 80° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0035] Then, the epoxy resin, curing agent and accelerator containing in-situ generated Cu2S nanoparticles reinforced filler were placed in a high-speed mixer, Al2O3 micron filler was added, and the mixture was stirred evenly at 80°C, and then observed whether the mixture was evenly dispersed. The mixture was then placed in a mold, degassed at 110°C for 30 minutes, and vacuum degassing was performed; 120°C for 90 minutes, then heated to 165°C for 110 minutes, and finally heated to 195°C for 100 minutes for high-temperature curing, and then demolded to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and the resistivity test was performed.
[0036] Example 3 A method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles comprises the following steps: First, prepare 100 parts of epoxy resin E51, 150 parts of Al2O3 micron base filler, 7 parts of N,N-dibutyl copper dithiocarbamate, 80 parts of maleic anhydride, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0037] In situ generated Cu2S nanoparticle reinforced filler, which is prepared by the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP (volume ratio of 1:1), keep the temperature at 80°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and copper N,N-dibutyldithiocarbamate into a reaction kettle, heating it to 180°C at a heating rate of 2°C / min, and then maintaining it at 180°C for 5 hours to complete the reaction; 4) After the above reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 80° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0038] Then, the epoxy resin, curing agent and accelerator containing in-situ generated Cu2S nanoparticles reinforced filler were placed in a high-speed mixer, Al2O3 micron filler was added, and the mixture was stirred evenly at 80°C, and then observed whether the mixture was evenly dispersed. The mixture was then placed in a mold, degassed at 110°C for 30 minutes, and vacuum degassing was performed; 120°C for 90 minutes, then heated to 165°C for 110 minutes, and finally heated to 195°C for 100 minutes for high-temperature curing, and then demolded to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and the resistivity test was performed.
[0039] Example 4 A method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles comprises the following steps: First, prepare 100 parts of epoxy resin E51, 150 parts of Al2O3 micron base filler, 15 parts of N,N-dibutyl copper dithiocarbamate, 80 parts of maleic anhydride, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0040] In situ generated Cu2S nanoparticle reinforced filler, which is prepared by the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP (volume ratio of 1:1), keep the temperature at 80°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and copper N,N-dibutyldithiocarbamate into a reaction kettle, heating it to 180°C at a heating rate of 2°C / min, and then maintaining it at 180°C for 5 hours to complete the reaction; 4) After the above reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 80° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0041] Then, the epoxy resin, curing agent and accelerator containing in-situ generated Cu2S nanoparticles reinforced filler were placed in a high-speed mixer, Al2O3 micron filler was added, and the mixture was stirred evenly at 80°C, and then observed whether the mixture was evenly dispersed. The mixture was then placed in a mold, degassed at 110°C for 30 minutes, and vacuum degassing was performed; 120°C for 90 minutes, then heated to 165°C for 110 minutes, and finally heated to 195°C for 100 minutes for high-temperature curing, and then demolded to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and the resistivity test was performed.
[0042] Example 5 A method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles comprises the following steps: First, prepare 110 parts of epoxy resin E42, 200 parts of Al2O3 micron base filler, 5 parts of N,N-dibutyl copper dithiocarbamate, 70 parts of hydrogenated phthalic acid, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0043] In situ generated Cu2S nanoparticle reinforced filler, which is prepared by the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP (volume ratio of 80:90), keep the temperature at 70°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and copper N,N-dibutyldithiocarbamate into a reaction kettle, heating to 160°C at a heating rate of 1.5°C / min, and then maintaining at 160°C for 6 hours to allow the reaction to be complete; 4) After the above reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 70° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0044] Then, the epoxy resin, curing agent and accelerator containing in-situ generated Cu2S nanoparticles reinforced filler were placed in a high-speed mixer, Al2O3 micron filler was added, and the mixture was stirred evenly at 70°C, and then observed whether the mixture was evenly dispersed. Then, the mixture was placed in a mold, degassed at 100°C for 45 minutes, and vacuum degassing was performed; 110°C for 110 minutes, then heated to 155°C for 130 minutes, and finally heated to 185°C for 120 minutes, and then demolded to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and the resistivity test was performed.
[0045] Example 6 A method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles comprises the following steps: First, prepare 110 parts of epoxy resin E42, 200 parts of Al2O3 micron base filler, 5 parts of N,N-dibutyl copper dithiocarbamate, 70 parts of hydrogenated phthalic acid, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0046] In situ generated Cu2S nanoparticle reinforced filler, which is prepared by the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP (volume ratio of 110:120), keep the temperature at 90°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and copper N,N-dibutyldithiocarbamate into a reaction kettle, heating to 200°C at a heating rate of 1.5°C / min, and then maintaining at 200°C for 6 hours to complete the reaction; 4) After the reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 90° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0047] Then, the epoxy resin, curing agent and accelerator containing in-situ generated Cu2S nanoparticles reinforced filler were placed in a high-speed mixer, Al2O3 micron filler was added, and the mixture was stirred evenly at 90°C, and then observed whether the mixture was evenly dispersed. Then, the mixture was placed in a mold, degassed at 120°C for 25 minutes, and vacuum degassing was performed; 130°C for 70 minutes, then heated to 175°C for 90 minutes, and finally heated to 205°C for 80 minutes for high-temperature curing, and then demolded to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and the resistivity test was performed.
[0048] Example 7 A method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles comprises the following steps: First, prepare 110 parts of epoxy resin E42, 200 parts of Al2O3 micron base filler, 5 parts of N,N-dibutyl copper dithiocarbamate, 70 parts of hydrogenated phthalic acid, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0049] In situ generated Cu2S nanoparticle reinforced filler, which is prepared by the following steps: 1) Dissolve the epoxy resin in a mixed solvent of DMF and NMP (volume ratio of 120:110), keep the temperature at 100°C, and stir thoroughly until the epoxy resin is dissolved in the solution; 2) Add N,N-dibutyl copper dithiocarbamate to the obtained epoxy resin solution, first disperse it evenly with a high-speed stirrer, and then disperse it again with a cutting-edge ultrasonic instrument; 3) placing the obtained mixed solution of epoxy resin and copper N,N-dibutyldithiocarbamate into a reaction kettle, heating to 190°C at a heating rate of 1.5°C / min, and then maintaining at 190°C for 5 hours to allow the reaction to be complete; 4) After the above reaction is completed, the mixed solution is stirred in a nitrogen atmosphere at 85° C. until the solvent is completely evaporated to obtain an epoxy resin containing in-situ generated Cu2S nanoparticle reinforced filler.
[0050] Then, the epoxy resin, curing agent and accelerator containing in-situ generated Cu2S nanoparticles reinforced filler were placed in a high-speed mixer, Al2O3 micron filler was added, and the mixture was stirred evenly at 85°C, and then observed whether the mixture was evenly dispersed. The mixture was then placed in a mold, degassed at 105°C for 35 minutes, and vacuum degassing was performed; 115°C for 100 minutes, then heated to 160°C for 120 minutes, and finally heated to 200°C for 110 minutes for high-temperature curing, and then demolded to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles, and the resistivity test was performed.
[0051] Comparative Example 1 100 parts of epoxy resin E51, 150 parts of Al2O3 micron base filler, 80 parts of maleic anhydride, 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0052] The measured epoxy resin E51, curing agent and accelerator are placed in a high-speed mixer, and Al2O3 micron base filler is added and stirred evenly, and then the mixture is observed to be evenly dispersed. The mixture is then placed in a mold, vacuum degassing and high-temperature curing are performed, and then demolding is performed to obtain an epoxy resin containing only Al2O3 micron base filler but not in-situ generated Cu2S nanoparticle reinforced filler, and the resistivity test is performed.
[0053] Table 1 Performance comparison of the products obtained in Examples 1-4 and Comparative Example 1
[0054] Table 1 is a performance comparison of the products obtained in Examples 1-4 and Comparative Example 1. It can be seen from Table 1 that the Cu2S nano-reinforced filler is generated in situ in the epoxy resin. The appropriate content can enhance the electrical and mechanical properties of the epoxy resin, and the comprehensive performance is good, which is suitable for high voltage DC applications.
[0055] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles, characterized in that: The invention comprises epoxy resin, filler, curing agent and accelerator; the filler comprises basic filler and reinforcing filler; the basic filler is Al2O3 micron particles; the reinforcing filler is Cu2S nanoparticles; the Cu2S nanoparticles are prepared by in-situ reduction of N,N-dibutyl copper dithiocarbamate in epoxy resin.
2. The high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 1, characterized in that: The mass ratio of the epoxy resin, Al2O3 micron particles, N,N-dibutyl copper dithiocarbamate, curing agent and accelerator is (90-110): (100-200): (3-15): (60-80):
1.
3. The high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 1, characterized in that: The epoxy resin is any one of bisphenol A epoxy resin E51 and bisphenol A epoxy resin E42.
4. The high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 1, characterized in that: The curing agent is any one of anhydride curing agent, tetrahydrophthalic acid, hydrogenated phthalic acid and maleic anhydride.
5. The high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 1, characterized in that: The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
6. The method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to any one of claims 1 to 5, characterized in that: include: The epoxy resin is dissolved in a mixed solvent of DMF and NMP, and is fully stirred until dissolved; N, N-dibutyl copper dithiocarbamate is added, stirred evenly at high speed, and secondary dispersion is performed by ultrasound; after the temperature is raised to react, the epoxy resin is heated and stirred until the solvent is completely volatilized to obtain an epoxy resin containing in-situ generated Cu2S nanoparticles reinforced filler; a curing agent, an accelerator and Al2O3 micron particles are then added, stirred evenly, placed in a mold, vacuum degassing and high-temperature curing are performed, and then demolding is performed to obtain a high-voltage direct current epoxy resin modified based on in-situ generated Cu2S nanoparticles.
7. The method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 6, characterized in that: The mass ratio of the epoxy resin, Al2O3 micron particles, N,N-dibutyl copper dithiocarbamate, curing agent and accelerator is (90-110): (100-200): (3-15): (60-80): 1; the volume ratio of DMF and NMP is (80-120): (80-120); the stirring temperature is 70-100°C.
8. The method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 6, characterized in that: The temperature-raising reaction conditions are: raising the temperature to 160-200° C. at a heating rate of 1-2° C. / min and keeping the temperature for 3-6 hours.
9. The method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 6, characterized in that: The heating and stirring temperature is 70-90°C; the vacuum degassing condition is: degassing at 100-120°C for 25-45min; the high temperature curing condition is: 110-130°C for 70-110min, then heating to 155-175°C for 90-130min, and finally heating to 185-205°C for 80-120min.
10. The method for preparing a high voltage direct current epoxy resin modified by in-situ generated Cu2S nanoparticles according to claim 6, characterized in that: 1 mol of N,N-dibutylcopper dithiocarbamate produces 1 mol of Cu2S nanoparticles.
Citation Information
Patent Citations
Nano-copper-containing epoxide resin composite material and preparation method thereof
CN103408896A
Preparation method of heat-conductive and flame-retardant material for lithium batteries
CN106147131A
Method for in-situ synthesis of silver sulfide nano particle reinforced polytetrafluoroethylene-based composite lubricating coating
CN110194931A
Production of metal sulfide
JP1989298008A